Insights into Financial Statement Audits and Assurance Practices - Ramlah Ramlah (Advances in Managerial Auditing Research, 2026)
Purpose: This study aims to provide a comprehensive examination of financial statement audits and assurance practices by enriching the understanding of key concepts, methodologies, and empirical findings in this field. Research Method: This research employed a qualitative literature review method. The study systematically analyzed scholarly works, theoretical frameworks, and empirical studies related to financial statement audits and assurance practices. The research process involved identifying relevant literature sources, collecting data, analyzing findings, and synthesizing recurring themes, empirical trends, and gaps in the existing literature. Results and Discussion: The findings highlight the importance of auditor independence, professional skepticism, and robust audit procedures in ensuring audit quality and the integrity of financial reporting. The study also shows that corporate governance mechanisms, regulatory reforms, and technological advancements play an important role in shaping audit practices. Implications: The findings emphasize the need for continuous professional development, stronger regulatory oversight, and investment in technological capabilities to improve audit quality, effectiveness, and relevance in a rapidly changing business environment. Future research is recommended further to examine emerging issues in audit and assurance practices. Originality: This study offers an integrated literature-based perspective on financial statement audits and assurance practices by synthesizing key concepts, empirical trends, and research gaps in the field.